2019
DOI: 10.1111/tbed.13271
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal analysis of peste des petits ruminants outbreaks in PR China (2013–2018): Updates based on the newest data

Abstract: Peste des petits ruminants (PPR) is a highly contagious disease of small ruminants.The purpose of this study was to investigate the epidemic characteristics of PPR outbreaks in the People's Republic of China (PR China) from 2013 to 2018. A total of 41,876 PPR outbreaks were recorded in small ruminant populations in PR China during that period. Data from February to June 2018 were used to study new developments in the PPR epidemic in PR China. Spatio-temporal clusters and temporal distribution patterns were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, the distribution of pig‐producing areas is not uniform across provinces. Together with the increasingly improved highway transport network nationwide, these actions resulted in the rapid expansion of live‐pig trading among different provinces (Gao, Liu, Zheng, Xiao, & Wang, 2019). Thus, this enabled that in a space of as little as few as 2 to 3 days, ASF‐infected livestock could be shipped from provinces of origin to other provinces in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distribution of pig‐producing areas is not uniform across provinces. Together with the increasingly improved highway transport network nationwide, these actions resulted in the rapid expansion of live‐pig trading among different provinces (Gao, Liu, Zheng, Xiao, & Wang, 2019). Thus, this enabled that in a space of as little as few as 2 to 3 days, ASF‐infected livestock could be shipped from provinces of origin to other provinces in China.…”
Section: Discussionmentioning
confidence: 99%
“…The following geographically distributed landscape, climate, and socio-economic characteristics for each administrative unit were selected as potential explanatory factors, based on an analysis of scientific publications on the spatial and temporal modelling of PPR (Cao et al, 2018;Gao et al, 2019;Lembo et al, 2013;Ma et al, 2017Ma et al, , 2019Mokhtari et al, 2017;Ruget et al, 2019): (1) Variables proxying an intensity of regional economic activity that may influence the disease spread by transport links-total road length, road density, average population density, and the Engel coefficient 1 ; (2) Average den- The performance of the obtained model was tested by predicting for the Chinese study region and comparing the observed and predicted number of PPR outbreaks. The regression residuals were tested for spatial autocorrelation using Moran's I test (Mitchell, 2005).…”
Section: Modelling Methodsmentioning
confidence: 99%
“…The following geographically distributed landscape, climate, and socio‐economic characteristics for each administrative unit were selected as potential explanatory factors, based on an analysis of scientific publications on the spatial and temporal modelling of PPR (Cao et al., 2018; Gao et al., 2019; Lembo et al., 2013; Ma et al., 2017, 2019; Mokhtari et al., 2017; Ruget et al., 2019): (1) Variables proxying an intensity of regional economic activity that may influence the disease spread by transport links— total road length, road density, average population density, and the Engel coefficient; (2) Average density of small ruminants and average cattle density as indicators of susceptible population's and other potential host's density; (3) Most general landscape and climatic factors that may shape a suitable habitat for small ruminants and provide favourable conditions for the virus spread— average elevation, annual mean temperature, annual precipitation, and maximum green vegetation fraction. To provide environmental and socio‐economic similarity between the study regions in China and Kazakhstan, we ensured that each variable's range overlapped for both countries.…”
Section: Methodsmentioning
confidence: 99%
“…Different sets of variables hypothesized to directly or indirectly facilitate/ support the PPR mode of transmission were considered in this study as supported by recent scholarly literature and specific epidemiological aspects of PPR virus transmission. PPR transmission and spread is usually facilitated by human socio-economic activities, bioclimatic conditions, topographic and environmental factors that tend to favour suitability of PPR disease occurrence (Gao et al, 2019). These factors, acting singly or in combination may contribute significantly to the transmission and spread of the PPR virus resulting into re-introduction or introduction of such infectious diseases into new areas.…”
Section: Preparation Of Potential Explanatory Variablesmentioning
confidence: 99%